Manusia sebagai Objek dan Subjek dalam Manajemen Sumber Daya Manusia Digital: Tinjauan Literatur Sistematis - Mari Maryati; Rita Sari Puspita; Isniar Budiarti; Siti Kurnia Rahayu; Dedi Sulistyo Soegoto (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2026)
Digital transformation in Human Resource Management is driving a shift in how organizations perceive the role of humans in the workplace. On one hand, the implementation of digital technology and artificial intelligence tends to position employees as economic objects measured and optimized through algorithmic systems. On the other hand, a human-centric approach places humans as active subjects possessing dignity, autonomy, and psychological needs. This study aims to analyze and synthesize the perspectives of humans as objects and subjects in digital HRM. The method utilized is a systematic literature review of reputable international journal articles. The analysis was conducted by comparing primary theoretical frameworks: Agency Theory and the Resource-Based View as representations of the human-as-object perspective, and Self-Determination Theory and Social Exchange Theory as representations of the human-as-subject perspective. Findings indicate that technology-based objective approaches can improve the efficiency and accuracy of HR management, but have the potential to cause dehumanization, decreased well-being, and employee resistance if applied excessively. Conversely, subjective approaches emphasizing autonomy, engagement, and reciprocal relationships are proven to support intrinsic motivation and sustainable performance. This study recommends the integration of human-centric approaches in digital HRM to balance organizational efficiency demands with human well-being in the Industry 5.0 era Keywords: Digital HRM; Human-Centricity; Algorithmic Management; Industry 5.0; Systematic Literature Review